The importance of the sports psychologist's role today: experience report (Research, Society and Development, 2018)
The purpose of this article is to present the role of the sports psychologist in the present time by means of an internship experience report by an academic of the Psychology course of a private teaching institution located in the city of Santa Maria, RS. The internship practices were carried out on the Santa Maria Soldiers football team, held at the Campus of the Federal University of Santa Maria (UFSM), and in the matches that were practiced at the Presidente Vargas Stadium. It was observed that providing psychological support to athletes is as essential as providing them with a balanced diet, performed by a nutritionist. Through this practice it is possible to verify the importance of the performance of the psychologist with the Santa Maria Soldiers football team, since it occupies the space destined to the scope of the sport, dedicated in improving the performance of the athletes, in guiding them, and to provide activities to improve physical and mental health of athletes. The internship experience reported in this study made it possible to understand how each athlete needs a specific motivation for high performance. It is concluded that helping athletes to achieve their maximum at the time of play and that there must be a mutual commitment in physical and emotional activities, both of psychologists and coaches as well as the athletes themselves.